CRISIS AND SURVIVAL OF THE HANDLOOM INDUSTRY IN KERALA - Sishina O C (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article looks into the innumerable challenges confronting the handloom sector in Kerala, a traditional industry that has persevered through time yet faces significant hurdles in the modern era. It explores how this vibrant industry is adapting and evolving, especially in the wake of the difficulties brought on by the Covid-19 pandemic. The piece provides an in-depth analysis of various obstacles impacting production processes and job creation within the sector. Additionally, it emphasises that the future of Kerala’s handloom industry hinges on the adoption of innovative strategies in product development and the critical need for the government to prioritize this sector in its policies and support initiatives.